A Linear Physical Programming Approach to Power Flow and Energy Storage Optimization in Smart Grids Models - Gabriella Dellino; Carlo Meloni; Saverio Mascolo (Proceedings of the International Conference on Operations Research and Enterprise Systems, 2015)
The Optimal Power Flow problem plays a crucial role in the successful energy management of modern smart grids. The diffusion of renewable energy sources poses new challenges to the power grid in which integrated energy storage combined with green generation solutions can help to address challenges associated with both power supply and demand variability. This work refers to a smart grid context and proposes a time-indexed optimal power flow model considering storage dynamics, adopting a preference-based optimization method with chance constraints to provide a suitable service level.